2016
DOI: 10.1039/c6ra11643d
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation and optimization of performance and emission characteristics of a DI diesel engine fueled with n-propanol/diesel, n-butanol/diesel and n-pentanol/diesel blends using response surface methodology

Abstract: High carbon bio-alcohols have recently grabbed the attention of diesel engine researchers because of higher energy density, higher cetane number and better blend stability than their low carbon counterparts. This study utilizes three high carbon bio-alcohol/diesel blends prepared by mixing 40% by vol. of n -propanol, n -butanol and n -pentanol individually with fossil diesel in a DI diesel engine. Engine performance and emission characteristics were measured under high-load condition based on a 3 3 full-factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…and Yilmaz et al (2016) also found that 10 and 20% pentanol/WCO biodiesel blends resulted in an improvement in BTE and a maximum of 2% increase in the BSFC. These findings are in agreement with the recent results by Mahalingam et al (2018) for 10 and 20% pentanol/Mahua oil methyl ester (MOME) blends and by Rajasekar (2016) for the Jatropha oil biodiesel/pentanol (B70B30) blend. However, in a single-cylinder water-cooled diesel engine fueled with Karanja oil biodiesel blends along with pentanol addition of 10 and 20% by volume (Jeyakumar and Narayanasamy, 2019), the BTE increased and BSFC decreased with binary blends.…”
Section: Performance Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…and Yilmaz et al (2016) also found that 10 and 20% pentanol/WCO biodiesel blends resulted in an improvement in BTE and a maximum of 2% increase in the BSFC. These findings are in agreement with the recent results by Mahalingam et al (2018) for 10 and 20% pentanol/Mahua oil methyl ester (MOME) blends and by Rajasekar (2016) for the Jatropha oil biodiesel/pentanol (B70B30) blend. However, in a single-cylinder water-cooled diesel engine fueled with Karanja oil biodiesel blends along with pentanol addition of 10 and 20% by volume (Jeyakumar and Narayanasamy, 2019), the BTE increased and BSFC decreased with binary blends.…”
Section: Performance Characteristicssupporting
confidence: 93%
“…CO and HC emissions of n-pentanol/WCO biodiesel blends are higher than those of diesel and biodiesel, particularly at low engine loads (Zhu et al, 2016). Similarly, Rajasekar (2016) found for Jatropha biodiesel/pentanol blends (B70P30) that smoke opacity and NOx emissions decreased while CO and HC emissions increased. Further, J70P30 resulted in lower CO, NOx, and PM emissions than J70BU30 (butanol) for all loads, while J70P30 produced higher HC emissions than J70BU30 for all loads.…”
Section: Combustion and Emission Characteristicsmentioning
confidence: 77%
“…In addition, increase in percentage of DTBP in KME lowers the ignition delay and enhances mixing of fuel and air. Consequently, the combustion rate is improved, which lowers the HC emissions (Kumar et al 2016). The above-depicted results are in harmony with the work of Devarajan et al…”
Section: Unburned Hydrocarbonssupporting
confidence: 89%
“…Increasing attention has been paid to the use of non-petroleum-based fuels, preferably from renewable sources, including alcohols with up to five carbon atoms. These alcohols are successful in the practical use as gasoline and diesel fuel additives and this has motivated the full investigation of their combustion chemistry [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Presented and published explosion ranges (in vol.%). Institut für Arbeitsschutz der Deutschen Gesetzlichen Unfallversicherung, Sankt Augustin, Germany,2 International Labour Organization, Geneva, Switzerland,3 Society of Fire Protection Engineers, Gaithersburg, USA,4 Design Institute for Physical Property Research, Fort Washington, USA, 5 1P + 2P = 1-C 3 H 7 OH + 2-C 3 H 7 OH mixture for f = 0.5.…”
mentioning
confidence: 99%